2012
DOI: 10.1590/s1982-56762012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Association of oxidative stress components with resistance to flax powdery mildew

Abstract: Field trials were conducted in 2008/2009 and 2009/2010 growing seasons at Giza Agricultural Research Station to evaluate powdery mildew (PM) severity on nine flax cultivars. Tested cultivars could be classified into five distinct groups, i.e., highly susceptible (Corland and C.I. 2008), susceptible (Giza 7 and Marshall), moderately susceptible (Cass), moderately resistant (Dakota, Koto and Wilden) and resistant (Ottowa 770B). They showed considerable variation in PM severity ranging from 8.1 on Ottowa 770B to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Table 1 clearly indicates that the maximum increase of -tocopherolwas found in varieties than hybridsthat could protects varieties more profitably than hybrids from oxidative damage caused by pathogens of foliar fungal disease complex. Similar increase of -tocopherol was found by Mohamed et al (2012) in nine flax cultivars while studying the association of oxidative stress components with resistance of flax against powdery mildew (PM) severity andspeculate that the increases in -tocopherol levels in infected leaf tissues may enhance flax resistance to PM by protecting cell membrane from oxidative damage.The result of present investigation also confirmatory with Avasthi (2014) who observed that concentration of vitamin E was increase in Aloe vera leaves infested with Colletotrichum gloeosporioides and Fusariummoniliforme fungal pathogens as compared to control leaves. Catalase (CAT) activity was declined in infected leaves of all cultivars over healthy leaves (Table 1).…”
Section: Resultssupporting
confidence: 53%
“…Table 1 clearly indicates that the maximum increase of -tocopherolwas found in varieties than hybridsthat could protects varieties more profitably than hybrids from oxidative damage caused by pathogens of foliar fungal disease complex. Similar increase of -tocopherol was found by Mohamed et al (2012) in nine flax cultivars while studying the association of oxidative stress components with resistance of flax against powdery mildew (PM) severity andspeculate that the increases in -tocopherol levels in infected leaf tissues may enhance flax resistance to PM by protecting cell membrane from oxidative damage.The result of present investigation also confirmatory with Avasthi (2014) who observed that concentration of vitamin E was increase in Aloe vera leaves infested with Colletotrichum gloeosporioides and Fusariummoniliforme fungal pathogens as compared to control leaves. Catalase (CAT) activity was declined in infected leaves of all cultivars over healthy leaves (Table 1).…”
Section: Resultssupporting
confidence: 53%
“…PPO catalyzes the oxidation of phenolics to free radicals, which can react with biological molecules, thus creating an unfavorable environment for pathogen development [12,39]. PPO activity was significantly different in healthy plants of all tested genotypes and maximum PPO activity was observed in healthy plants of MH-933 ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The PPO catalyzes the oxidation of phenolics to free radicals that can react with biological molecules, thus creating an unfavorable environment for pathogen development (Jockusch, 1966;Mohamed et al, 2012). The PPO activity was found to increase in leaves of BBTV-infected plants of tested cultivars (Fig.…”
Section: Polyphenol Oxidase (Ppo)mentioning
confidence: 97%